A study of knowledge of Anganwadi workers regarding minor ailments among children in Amritsar district of Punjab, India - Kaur, Harpreet; Kaur, Amanpreet; Kaur, Harpreet; Devgun, Priyanka (International Journal Of Community Medicine And Public Health, 2017)
Background: Anganwadi workers (AWW) are India’s primary tool against the menace of child malnourishment, infant mortality, and lack of child education, community health. The anganwadi workers should have basic knowledge of treatment of minor ailment. So with this aim this study was planned to assess the existing knowledge regarding minor ailments of children among anganwadi workers problems and in curbing preventable diseases. Methods:The present study was conducted in the Department of Community Medicine SGRDIMSAR, Amritsar. By adopting stratified random sampling technique, 5 AWW were selected per each training session. A pre- designed and pre-tested questionnaire prepared was used to collect information from AWW. Pre-test and post-test assessment to determine the knowledge of minor ailments among AWW was done. The data collected was statistically analysed using SPSS 20.0 version. Results: The study revealed that out of 135 AWW, 40% were in the age group of 25-45 years. Only 8.9% AWW were aware that a neonate should be referred in case he suffers from any of these conditions i.e. hypothermia, jaundice, fever. Awareness about newborn care practices was observed to increase with increase in education level. There was statistically significant improvement in the knowledge regarding minor ailments in post-test scores of AWWs. Conclusions:Anganwadi workers are India’s primary tool against the scourges of child malnourishment, infant mortality and curbing preventive diseases such as most minor ailments.